2019
DOI: 10.1183/16000617.0084-2019
|View full text |Cite|
|
Sign up to set email alerts
|

Central sleep apnoea and periodic breathing in heart failure: prognostic significance and treatment options

Abstract: Central sleep apnoea (CSA) including periodic breathing is prevalent in more than one-third of patients with heart failure and is highly and independently associated with poor outcomes. Optimal treatment is still debated and well-conducted studies regarding efficacy and impact on outcomes of available treatment options are limited, particularly in cardiac failure with preserved ejection fraction. While continuous positive airway pressure and oxygen reduce breathing disturbances by 50%, adaptive servoventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
0
18
0
1
Order By: Relevance
“…CSA is uncommon in the general population compared to OSA (23) but is common in specific subpopulations of patients, including those with heart failure (24,25), stroke (26), and during opioids administration (27). CSA can be also diagnosed in other conditions, or can be defined as idiopathic, according to the International Classification of Sleep Disorders (3rd edition) (ICSD-3) (28).…”
Section: Csamentioning
confidence: 99%
“…CSA is uncommon in the general population compared to OSA (23) but is common in specific subpopulations of patients, including those with heart failure (24,25), stroke (26), and during opioids administration (27). CSA can be also diagnosed in other conditions, or can be defined as idiopathic, according to the International Classification of Sleep Disorders (3rd edition) (ICSD-3) (28).…”
Section: Csamentioning
confidence: 99%
“…Pulmonary congestion can activate pulmonary C-fibers in the lung parenchyma, which leads to chronic hyperventilation and unstable breathing. It has been shown that CSA worsens the prognosis of patients with systolic dysfunction (2).…”
Section: Case Conferences Discussionmentioning
confidence: 99%
“…CSR/B refers to the historical description of periodic breathing (PB) with apnoeas in HF/stroke (5). PB; CSA due to high altitude PB; CSA due to a medication or substance; primary CSA; treatment-emergent CSA (6).…”
Section: Cheyne-stokes Respiration/breathingmentioning
confidence: 99%
“…The recent RCTs show challenging results on current pathophysiology understanding of CSA, and the effects of currently available therapies on clinical outcome are ongoing research (12). Several strategies have been considered for improvement of the ventilation (5).…”
Section: Management Of Csa In Hfmentioning
confidence: 99%
See 1 more Smart Citation